STRENGTHENING THE FUNCTIONS OF FARMER GROUPS IN THE MANUFACTURE AND USE OF VEGETABLE WASTE MOL IN PLANTS (MUSTARD GREENS, SPINACH) - Nurdiyanawati Djumadil; Yunus Syafie (Bajang Institute, 2021)
Farmer groups are farmer institutions that have a strategic role in supporting the success of agricultural activities and as subjects of sustainable agricultural development. However, in general, the roles and functions of farmer groups as learning classes, vehicles for cooperation, and production units do not work as they should. As is the case with Tanjung Selatan farmer groups. The purpose of this service activity is to help raise awareness of farmers in farmer groups as partners so that they want, know, and adopt science, skills, and technology in producing organic fertilizers in the form of Local Micro Organisms (MOL vegetable waste) that are environmentally friendly. The implementation of this PKM activity uses a socialization and training approach as well as its application starting from the preparation of materials to the processing process into vegetable waste MOL fertilizer products that are ready to be used on kale, mustard and spinach plants which can reduce the use of chemicals so that the vegetables produced have good quality.